Vidas de professoras: um contributo para o estudo das relações entre percursos de vida e ação pedagógica - Sousa, Rosane Aleluia Santos de (2011)
Teachers' lives: a contribution to the study of relations between course and pedagogical action. It is a work that presents reflections on the stories told by some literacy teachers to understand the relationship between life courses and pedagogical action of these professionals. The work is divided into five parts, the first is the introduction, there are presented the elements influencing the choice that led to that theme and purpose of work. The second part about is divided into four chapters. The first chapter is presented in narrative form the author's life story and how she became a teacher, professional life and the concerns that have arisen in the course of practice as a teacher in the Faculty of Education. The second chapter deals with the trajectory of approach of life history in the last twenty years to be considered as research approach. It also presents relevant points of the studies that have been developed by Marie- Christine Josso, Antonio Nóvoa, Clementino Eliseu de Souza and others who study the same subject and who have contributed significantly in systematic work about the life histories, autobiographies and in the learning experiences built by the authors during their research. In a subsequent chapter presents the reflections on the outcome of the records of students' narratives of the pedagogy course on the stages of childhood, adolescence and adulthood. In this chapter, there is a concern with using narrative as a form of reflection that expresses remembers that are in memory of the person and which have substantial elements in the path of personal and professional life. The last chapter is set aside for closing remarks, where is evidenced the importance of life story as a way to encourage reflection on formative experiences, on a deeper knowledge of self and an attempt to understand the relationship between life course and its relationship with educational praxis.